Novel aspinolide production by Trichoderma arundinaceum with a potential role in Botrytis cinerea antagonistic activity and plant defence priming. (25th June 2014) - Malmierca, Mónica G.; Barua, Javier; McCormick, Susan P.; Izquierdo‐Bueno, Inmaculada; Cardoza, Rosa E.; Alexander, Nancy J.; Hermosa, Rosa; Collado, Isidro G.; Monte, Enrique; Gutiérrez, Santiago
Summary Harzianum A (HA), a trichothecene produced by Trichoderma arundinaceum, has recently been described to have antagonistic activity against fungal plant pathogens and to induce plant defence genes. In the present work, we have shown that a tri5 gene‐disrupted mutant that lacks HA production overproduces two polyketides, aspinolides B and C, which were not detected in the wild‐type strain. Furthermore, four new aspinolides (D–G) were characterized. These compounds confirm that a terpene‐polyketide cross‐pathway exists in T. arundinaceum, and they may be responsible for the antifungal activity and the plant sensitization effect observed with the tri5‐disrupted mutant. In addition, the molecular changes involving virulence factors in the phytopathogenic fungus Botrytis cinerea 98 (Bc98) during interaction with T. arundinaceum were investigated. The expression of genes involved in the production of botrydial by Bc98 was relatively repressed by HA, whereas other virulence genes of this pathogen were induced by the presence of T. arundinaceum, for example atrB and pg1 which encode for an ABC transporter and endopolygalacturonase 1 respectively. In addition, the interaction with Bc98 significantly repressed the production of HA by T. arundinaceum, indicating that a bidirectional transcriptional regulation is established between these two antagonistic fungi.